Pulmonary Embolism as a Complication after radiofrequency catheter ablation Study: A Case Report - Mahnaz Mozdourian; Fariba Rezaeetalab (Journal of Cardio-Thoracic Medicine, 2019)
Pulmonary thromboembolism (PTE) is a fatal condition that may rarely occur due to complications of coronary catheter insertion. In this case report, a 41-year-old male was presented 48 hours after radiofrequency catheter ablation(RFCA) for the management of Wolf-Parkinson-White syndromewith acute onset of dyspnea, hemoptysis, and chest pain. The physical examination revealed coarse crackles in the base of left hemithorax and laboratory tests were normal. The patient was suspicious for PTE based on clinical symptoms and the history ofRFCA. Diagnosis was confirmed by computed tomography angiography of lungs. Patient symptoms improved after 3 months of treatment with warfarin